2012
DOI: 10.1016/j.thromres.2011.06.025
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study utilizing whole body 18 F-FDG-PET/CT as a comprehensive screening strategy for occult malignancy in patients with unprovoked venous thromboembolism

Abstract: Background Approximately 7-10% of patients with unprovoked VTE will be diagnosed with cancer within 12 months. Although cancer screening has been proposed in these patients, the optimal strategy remains unclear. In a pilot study, we prospectively investigated the use of FDG-PET/CT to screen for occult malignancy in 40 patients with unprovoked VTE. Materials/Methods Patients were initially screened for occult malignancy with a focused history, physical, and laboratory evaluation. Patients underwent whole body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Herein, we report a S and Sp of FDG‐PET/CT for the detection of occult malignancy in selected patients with unprovoked VTE of 77.8 and 73.3%, respectively, with a PPV and NPV of 22.6 and 97.1%. This NPV is similar to that obtained in a recent pilot study, initiated after the beginning of our study, including only 40 patients without age limitations, in which just a single case of cancer (2.5%) was detected …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Herein, we report a S and Sp of FDG‐PET/CT for the detection of occult malignancy in selected patients with unprovoked VTE of 77.8 and 73.3%, respectively, with a PPV and NPV of 22.6 and 97.1%. This NPV is similar to that obtained in a recent pilot study, initiated after the beginning of our study, including only 40 patients without age limitations, in which just a single case of cancer (2.5%) was detected …”
Section: Discussionsupporting
confidence: 90%
“…Its application for the detection of occult cancer in patients with VTE could simplify the search. In a recent pilot study in a small and heterogeneous population, the use of FDG‐PET/CT as solitary screening tool for occult malignancy proved feasible with acceptable S …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three articles were selected and retrieved in fulltext version (Figure 1). One study was found screening the references [6] and 18 articles were subsequently excluded [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Finally, 16 studies were included [6,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] .…”
Section: Resultsmentioning
confidence: 99%
“…Cost study Rondina et al [24] 2012 United States Occult (various) Cost study Table 2 Characteristics of excluded studies Annunziata S et al . Cost-effectiveness of PET in oncology patient.…”
Section: Colon-rectum (Various)mentioning
confidence: 99%